Vascular Pathology in Alpha 1 Antitrypsin Deficient Chronic Obstructive Pulmonary Disease and Emphysema Patients: Case Reports - Gordon M; Gangemi AJ; Sandwith EL; Kumaran M; Kueppers F (The Application of Clinical Genetics)
Matthew Gordon,1,* Andrew J Gangemi,1,* Eric L Sandwith,2,* Maruti Kumaran,3,* Friedrich Kueppers1,* 1Department of Thoracic Medicine and Surgery, Lewis Katz School of Medicine at Temple University, Philadelphia, PA, USA; 2HCA Florida Heart and Lung, Fort Walton-Destin Hospital, Wright, FL, USA; 3Department of Radiology, Lewis Katz School of Medicine at Temple University, Philadelphia, PA, USA*These authors contributed equally to this workCorrespondence: Friedrich Kueppers, Department of Thoracic Medicine and Surgery, Lewis Katz School of Medicine at Temple University, Philadelphia, PA, USA, Email friedrich.kueppers@tuhs.temple.eduAbstract: Alpha 1 Antitrypsin Deficiency (AATD) is a genetic condition that results from mutations in the SERPINA1 gene, which can lead to deficient or dysfunctional Alpha 1 Antitrypsin (AAT) protein production. AATD is linked to chronic obstructive pulmonary disease (COPD) and emphysema. In addition to pulmonary manifestations, AATD has also been associated with vascular pathology due to excessive protease activity, tissue degradation, and vessel stiffening. Early AATD diagnosis is crucial to prevent progressive lung damage and associated pathologies. Here, we present case reports of two patients with AATD from the Temple University Hospital Outpatient Clinic, who exhibited aneurysms of the aorta and splenic artery. AATD should be considered a genetic risk factor for aneurysms and vascular diseases, necessitating cardiovascular monitoring in affected individuals. This report emphasizes both the need for heightened awareness of AATD as a potential etiology of unexplained vascular aneurysms, as well as the need for screening for vascular pathology in patients with AATD-associated COPD and emphysema to facilitate early intervention and improve patient outcomes.Keywords: alpha 1 antitrypsin, lung disease, aneurysm, aneurysm disease, vascular pathology, vascular disease